36 Urachal Adenocarcinoma Presenting in the Cervix. (11th January 2018) - Reddy, Amit; Poosarla, Teja; Kaur, Jaswinder; Henegan, John
Abstract: Urachal adenocarcinoma is an unusual non-urothelial bladder malignancy that often presents at advanced stages with poor prognosis. It is a rare malignancy accounting for an estimated 0.01% of all adult cancers and 0.5%-2.0% of all bladder malignancies. It is important to recognize the diagnosis earlier due to the differences in treatment options in comparison to urothelial carcinoma. We present a case of urachal adenocarcinoma with cervical involvement. A 42 year-old African American woman presented for evaluation due to a one-month history of abdominal pain and spotting. On physical examination, a large, firm, immobile cervical mass was present with necrotic debris filling the vagina. Grossly, the mass seemed to arise from the cervix. A biopsy of the mass was performed demonstrating moderately differentiated mucinous adenocarcinoma, an uncommon type of primary cervical carcinoma. Immunohistochemistry (IHC) studies showed malignant cells positive for CK20, CK7, CDX-2, and CEA; membrane and cytoplasmic staining for beta-catenin; and no nuclear translocation of beta-catenin protein. It was a challenge to differentiate between urachal adenocarcinoma and colorectal carcinoma because both stain positive for beta-catenin. A subsequent CT scan showed right-sided hydronephrosis, a 7.6 x 5.7 cm mass extending from the cervix to the uterus, and a 4.4 x 3.5 cm exophytic mass extending from the bladder dome. Since the IHC showed CK7 and cytoplasmic beta-catenin positivity as well as a CT with mass at the bladder dome, a diagnosis of primary urachal adenocarcinoma was confirmed. Diagnosing urachal carcinoma from a cervical mass metastasis is very unusual. Establishing a primary diagnosis proves difficult, since no specific markers have been established to differentiate urachal adenocarcinoma from colorectal adenocarcinoma. More specific IHC markers for future detection and cytologic diagnosis are needed to further characterize metastatic urachal adenocarcinoma.